A review of the Indian species of Apochinomma Pavesi, 1881 and Corinnomma Karsch, 1880, synonymy of Castianeira quadrimaculata Reimoser, 1934, and a catalogue of the Indian corinnid fauna (Arachnida: Araneae) - Sankaran, Pradeep M. (Zootaxa, 2021)
Indian species of the genera Apochinomma Pavesi, 1881 and Corinnomma Karsch, 1880 are reviewed. Corinnomma rufofuscum Reimoser, 1934 syn. nov. is synonymised with A. nitidum (Thorell, 1895). Redescriptions of A. nitidum and C. severum (Thorell, 1877) are provided, and two colour morphs (brown and black) of A. nitidum are illustrated. Supplementary descriptions for A. dolosum Simon, 1897 and C. comulatum Thorell, 1891 are provided. The species Castianeira quadrimaculata Reimoser, 1934 syn. nov. is recognised as a junior synonym of Coenoptychus pulcher Simon, 1885. Images of all the examined type material are provided and a catalogue of Indian corinnid species is presented.